AUTOMATE DEPLOYMENT APLIKASI WEB MENGGUNAKAN METODE GITOPS PADA KUBERNETES CLUSTER (STUDI KASUS: WEB RISET INFORMATIKA UNIVERSITAS MUHAMMADIYAH MALANG) - Fachry Fathurahman; Agus Eko Minarno; Mahar Faiqurahman (Elektrika Borneo, 2023)
The increase in internet users requires web services to have High Availability, which is the ability of web services to serve users and reduce downtime in the shortest possible time. One of the factors that can increase downtime is during the deployment process. Repetitive and manual deployment processes will be very vulnerable to human errors which will have an impact on downtime. On Informatics research website of the Muhammadiyah University of Malang is still implementing web services without using automation in deployment and also not using web containerization. In this study, the researcher designed a server environment that supports the two previously mentioned, by implementing Jenkins server as a CI/CD tool, cluster kubernetes as an orchestration container, and Github as a repository that supports the GitOps method, as a source of truth. This study tested 4 Informatics research website of the Muhammadiyah University of Malangg in automate deployment and got an average time of 126.74 seconds to build, push, and deploy